Medical students’ challenges and suggestions regarding research training: a synthesis of comments from a cross-sectional survey - Riva, John J.; Elsharawi, Radwa; Daza, Julian; Toma, Augustin; Whyte, Robert; Agarwal, Gina; Busse, Jason W. (Canadian Medical Education Journal, 2019)
Background: We previously reported on a cross-sectional study of students from the Michael G. DeGroote School of Medicine at McMaster University that found most respondents wanted more opportunities to participate in research. Students provided additional comments that we synthesized to enrich the findings of our quantitative analysis. Methods: From our previously administered 13-item, online questionnaire, run across three campuses in Ontario, Canada, 498 of 618 medical students completed our survey and 360 (72%) provided optional written comments, which we synthesized using thematic analysis in this current study. Results: Major themes that emerged were: (1) Active student participation to identify research opportunities and interested mentors are needed; (2) Types of research involvement; (3) Uncertainty whether research training translates into useable skills; (4) Desire for a formalized research curriculum and centralization of research opportunities across campuses. Conclusion: Programs should stress to interested students the importance of actively looking for research opportunities and consider both large and small-group educational sessions.